Analisis Kesulitan Belajar Matematika pada Siswa SMP di Masa Pandemi Covid-19 - Nanang Setiawan; Putri Nur Azizah; Vara Erni Yuanita; Viki Masruroh; Pebriani Rahmawati; Seftiana Mardikasari W; Darmadi Darmadi (Universitas Pahlawan Tuanku Tambusai, 2021)
The Covid-19 pandemic has had an impact on various fields, one of which is in the field of education. During this pandemic, face-to-face learning in class did not run properly, turning into an online learning system. This study aims to describe students' learning difficulties, especially mathematics at the junior high school level during the pandemic. The type of research used is descriptive qualitative. The instrument used is an online questionnaire. The conclusion of this study is that most students use WhatsApp as an online learning medium. The most common obstacles experienced by students during online learning are due to the lack of internet network constraints in some student places and internet quotas. In addition, mathematics also becomes its own difficulties and challenges for students when learning online due to several factors, namely: (1) too many math problems are given, (2) limited space for interaction with teachers, (3) abstract objects studied, (4 ) too many formulas.